ENDOSCOPIC INTERVENTIONS IN THE PATHOLOGY OF ARTIFICIAL ESOPHAGUS - E. A. Drobyazgin; Yu. V. Chikinev; I. E. Sudovikh (Вестник хирургии имени И.И. Грекова, 2018)
The  OBJECTIVE  of the  study  is to assess the  possibilities of using  endoscopic techniques in the  treatment of diseases of  the  artificial  esophagus. MATERIAL AND METHODS.  Esophagoplasty for  benign   diseases of  the  esophagus  was performed in 184  patients. 73  patients were  diagnosed with diseases of the  artificial esophagus and  underwent various endoscopic  interventions. RESULTS.   Restoring patency of  the  anastomosis was  achieved in  all  cases of  esophageal anastomotic stenoses   (68).   No   complications  were   observed.   Endoscopic  interventions  in  other   diseases  of  the artificial  esophagus allowed   improving  the  quality  of  life,  restoring patency  or  preparing  the  patient   for  intervention. CONCLUSION.  Endoscopic methods of treatment of diseases of the artificial esophagus are highly effective, allowing to  restore patency of the  artificial esophagus and  esophageal anastomoses.  These interventions should  be  carried  out in the specialized departments.